Analisis Dampak Lingkungan Hidup Pada Pelaku Usaha Kocokin Chicken Madura Kabupaten Bangkalan Desa Tellang - Nurul Fazirah (Jurnal Manajemen Riset Inovasi, 2024)
Environmental impact analysis on business actors is sometimes considered unimportant in good and correct waste management, causing negative impacts on the surrounding environment. Because of these problems, this research took a case study of Kocokin Chicken business actors in Bangkalan Regency, Telang Village, Madura. Qualitative research methods with primary data types through interviews and observations are used to directly identify the processing process of selling products. The results found show that there are various types of solid and liquid waste that have not been managed properly. Therefore, having good waste management alternatives, such as improving waste management infrastructure, can prevent sustainable environmental damage and improve the quality of life of local communities.